Digital Era Innovation: Utilization of Audio-Visual Barcode as a Digital Literacy Medium for Visitors in the Context of Education at the Surabaya Education Museum - Rizqa Maulida; Elysia Dyah Puspitasari; Yushofi Nur Amalina (Biokultur, 2026)
Digital transformation has changed the way museums interact with visitors, particularly in providing interactive and relevant learning experiences for the digital generation. The Surabaya Education Museum, as an institution dedicated to preserving the history of education, faces the challenge of engaging visitors through the presentation of a collection that has long been dominated by statistical data. This study employs a conceptual approach using a literature review to develop a model for utilizing audio-visual barcodes as a medium for visitors’ digital literacy. Data was analyzed through a process of reduction, categorization, and interpretation, focusing on the harmonization between visitors, educational content, and digital technology. The research results indicate that audio-visual barcode technology can enhance visitors’ digital literacy by providing interactive and easily accessible multimedia content, thereby creating a more dynamic and flexible learning experience. Although there are still limitations in the comprehensiveness of information presentation, this innovation serves as an effective first step toward strengthening the educational function of museums in the digital age and bridging historical heritage with new generations. The utilization of this technology also aligns with several Sustainable Development Goals (SDGs), particularly SDG 4, SDG 9, and SDG 11. Audio-visual barcode technology supports quality education, digital infrastructure innovation, and cultural preservation, making museums inclusive and sustainable educational institutions.